TEACHING OF GENERAL PHYSICS FOR MATHEMATICS PHYSICS TEACHERS’ TRAINING. AN INTERDISCIPLINARY APPROACH. - Pérez Rodríguez, Ángel Alberto; Sánchez Serra, Rita Caridad (Atenas, 2015)
The qualities that are required in the Model of professional for Mathematics Physics teachers’ training need a conception of the disciplines of the curriculum that take into account interdisciplinary. Teaching of General Physics must bear in mind the contents of Mathematical Analysis to deep on physical contents and to systematize the correspondents to the Mathematical Analysis. In this work one presents methodological suggestions for teaching General Physics and examples of solved problems that can be proposed in the lectures or practical lessons.